2017
DOI: 10.1021/acs.jafc.6b05816
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity and Oral Tolerance of Enzymatic Cross-Linked Tropomyosin Evaluated Using Cell and Mouse Models

Abstract: The enzymatic cross-linking of proteins to form high-molecular-weight compounds may alter their sensitization potential. The IgG-/IgE-binding activity, digestibility, allergenicity, and oral tolerance of cross-linked tropomyosin with tyrosinase (CTC) or horseradish peroxidase (CHP) were investigated. ELISA results demonstrated CTC or CHP reduced its IgE-binding activity by 34.5 ± 1.8 and 63.5 ± 0.6%, respectively. Compared with native tropomyosin or CTC, CHP was more easily digested into small fragments; CHP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 39 publications
6
45
0
Order By: Relevance
“…Sixty female BALB/c mice (aged 6–8 weeks, weighted 18–22 g) were purchased from and housed in the Laboratory Animal Center of Hangzhou Normal University (Hangzhou, China) and fed a basic diet (XIETONG ORGANISM, China) (Table S1, Supporting Information). Groups of 10 mice were treated according to the sensitization protocol, with the challenge and therapeutics performed according to Liu et al., [ 33 ] and the protocol is illustrated in Figure 1 A. In brief, each mouse was immunized by intragastric gavage (IG) administration of purified TM (3 mg for sensitization and 9 mg for challenging each time), together with recombinant cholera toxin subunit B (CTB, 250 µg each time) as an adjuvant, for a total of 200 µL of PBS, as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Sixty female BALB/c mice (aged 6–8 weeks, weighted 18–22 g) were purchased from and housed in the Laboratory Animal Center of Hangzhou Normal University (Hangzhou, China) and fed a basic diet (XIETONG ORGANISM, China) (Table S1, Supporting Information). Groups of 10 mice were treated according to the sensitization protocol, with the challenge and therapeutics performed according to Liu et al., [ 33 ] and the protocol is illustrated in Figure 1 A. In brief, each mouse was immunized by intragastric gavage (IG) administration of purified TM (3 mg for sensitization and 9 mg for challenging each time), together with recombinant cholera toxin subunit B (CTB, 250 µg each time) as an adjuvant, for a total of 200 µL of PBS, as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, Liu et al [69] attempted the cross-linking of crab tropomyosin to horseradish peroxidase or tyrosinase to produce CHP and CTC, respectively. Comparatively, the reduction of IgE-binding activity of CHP was more prominent than CTC, as suggested by the >60% reduction in IgE binding in ELISA and histamine release in RBL degranulation assay.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…A report showed that shrimp tropomyosin having a molecular weight of 36 kDa treated with Tyr produced higher molecular weight polymers (over 66 kDa). 13,28 The decrease in the densities, escorted by the appearance of high molecular weight smears were presumed to be the crosslinks. New bands with a molecular weight of ∼24, ∼36 kDa and above, were most obvious, as the PV was treated with CA ( Fig.…”
Section: Sds-page Analysis Of Tyr Crosslinked Pvmentioning
confidence: 99%